2020
DOI: 10.1002/anie.202000505
|View full text |Cite
|
Sign up to set email alerts
|

Poly(2‐Oxazoline)‐Based Functional Peptide Mimics: Eradicating MRSA Infections and Persisters while Alleviating Antimicrobial Resistance

Abstract: Peptides have important biological functions. However, their susceptibility to proteolysis limits their applications. We demonstrated here for the first time, that poly(2‐oxazoline) (POX) can work as a functional mimic of peptides. POX‐based glycine pseudopeptides, a host defense peptide mimic, had potent activities against methicillin‐resistant S. aureus, which causes formidable infections. The POX mimic showed potent activity against persisters that are highly resistant to antibiotics. S. aureus did not deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
145
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 190 publications
(151 citation statements)
references
References 80 publications
6
145
0
Order By: Relevance
“…[ 5 ] They demonstrated excellent potential as new therapeutic agents [ 6 ] because they are effective against antibiotic‐resistant bacteria, thanks to their mechanism of action. [ 7 ] Indeed, whereas common antibiotics interact with enzymes and/or receptors, AMPs and many other natural peptides act by physically disrupting or making permeable the membrane of the targets. [ 8 ] In addition, AMPs rapidly decompose when dispersed in the environment as they consist exclusively of α‐amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…[ 5 ] They demonstrated excellent potential as new therapeutic agents [ 6 ] because they are effective against antibiotic‐resistant bacteria, thanks to their mechanism of action. [ 7 ] Indeed, whereas common antibiotics interact with enzymes and/or receptors, AMPs and many other natural peptides act by physically disrupting or making permeable the membrane of the targets. [ 8 ] In addition, AMPs rapidly decompose when dispersed in the environment as they consist exclusively of α‐amino acids.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we proposed that poly(2‐oxazoline)s can work as a class of functional mimics of peptides and proved this hypothesis by mimicking HDP with poly(2‐oxazoline) to have potent antimicrobial properties (Figure 3e) [8a] . The HDP‐mimicking poly(2‐oxazoline)s, as a new class of peptide mimics in addition to β‐peptides, [12a] α‐peptoids, [11b] α‐AA and γ‐AA peptides [13] (Figure 3a‐3e), addressed natural peptides’ prominent shortcoming of instability upon proteolysis in vivo .…”
Section: Introductionmentioning
confidence: 93%
“…b–e) The structural design and synthesis of peptide mimicking peptoids, poly‐β‐peptide, AA‐peptides and poly(2‐oxazoline). Reprinted with permission from the reference [8a,12c,13,15] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, both the PHMB and guanidinium-functionalized polymers have the guanidinium functional groups, which may contribute to the cell-penetrating effect of these cationic polymers. Recently, Liu et al reported that cationic poly(2-oxazoline) selectively killed S. aureus (Zhou et al, 2020), engaging in strong interaction with DNA at low concentration, which results in producing ROS to damage the membrane and kill the bacteria. Duarte et al isolated an AMP ruminococcin C1 (RumC1) from human gut symbiont (Chiumento et al, 2019), which displayed similar phenotype as metronidazole that acts through inhibition of nucleic acid synthesis.…”
Section: Targeting the Intracellular Moleculesmentioning
confidence: 99%